2015
DOI: 10.1152/ajpheart.00180.2015
|View full text |Cite
|
Sign up to set email alerts
|

Impaired compensation to femoral artery ligation in diet-induced obese mice is primarily mediated via suppression of collateral growth by Nox2 and p47phox

Abstract: The present study was undertaken to establish the role of NADPH oxidase (Nox) in impaired vascular compensation to arterial occlusion that occurs in the presence of risk factors associated with oxidative stress. Diet-induced obese (DIO) mice characterized by multiple comorbidities including diabetes and hyperlipidemia were used as a preclinical model. Arterial occlusion was induced by distal femoral artery ligation in lean and DIO mice. Proximal collateral arteries were identified as the site of major (∼70%) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…Recent evidence demonstrated that NADPH oxidases NOX2 and NOX4 were increased by an HFD. 23 Accordingly, real-time quantitative RT-PCR and Western blot analysis showed that Nox2 and Nox4 levels were upregulated in hind-limb muscles from WT mice fed an HFD but not in p40 À/À and p35 À/À mice fed an HFD (Figure 6, CeF). We could not detect Nox1 expression in ischemic limb muscle from all mice.…”
Section: Resultsmentioning
confidence: 93%
“…Recent evidence demonstrated that NADPH oxidases NOX2 and NOX4 were increased by an HFD. 23 Accordingly, real-time quantitative RT-PCR and Western blot analysis showed that Nox2 and Nox4 levels were upregulated in hind-limb muscles from WT mice fed an HFD but not in p40 À/À and p35 À/À mice fed an HFD (Figure 6, CeF). We could not detect Nox1 expression in ischemic limb muscle from all mice.…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, adoptive transfer of Ly6C lo monocytes did not alter perfusion recovery or angiogenesis in contrast to adoptive transfer of Ly6C hi monocytes 38 41 . However, other studies have implied a role of the Ly6C lo monocyte population in both angiogenesis and arteriogenesis 42 43 44 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Genetic mapping comparing the two strains at the extremes of the distribution for collateral arteriogenesis restrained the possible differences to a few genetic loci, though no candidate gene that explains the differences has been identified (102). Hypercholesterolemia (103,104), obesity (105), and aging (106) also compromise arteriogenesis in mouse models. Thus, poor flow-dependent remodeling in human arterial disease is likely to have multiple causes, potentially requiring personalized treatment.…”
Section: Collateral Growth and Flow-dependent Remodelingmentioning
confidence: 99%